Neural Plasticity during Aging - Arcos-Burgos, Mauricio; Lopera, Francisco; Sepulveda-Falla, Diego; Mastronardi, Claudio (Journal of neural transplantation & plasticity, 2019)
[...]the incidence of neurodegenerative diseases will continue to rise as a result of the increase in life expectancy. [...]approximately two decades ago, it became evident that a new type of neuroplasticity, one that is related to the addition of new neurons, occurs in the human brain [8, 9]. The understanding of the impact they exert particularly on the brain, and generally on the body, may aid in the development of novel therapeutic strategies to overcome the deleterious effects occurring during the aging process. [...]there is an increased need to expand the knowledge on the different genetic, epigenetic, and molecular pathways and environmental factors that affect brain plasticity and healthy aging. In their original mouse study, S. Cintoli et al. described for the first time the protective role of environmental enrichment in preventing declarative learning and memory decline in aged mice. [...]their exciting results in mice suggest that exposure to stimulating environmental conditions could be used as a powerful paradigm to promote better memory performance during aging in the elderly population.